Adaptation of a Voice-Centered Relational Framework to Explore the Perspective of Parents Who Have Transitioned to Home with a Child With Complex Care Needs. Issue 4 (2nd October 2017) - Brenner, Maria; Connolly, Michael; Larkin, Philip J.; Hilliard, Carol; Howlin, Frances; Cawley, Des
ABSTRACT: Parents of children with complex care needs are generally willing to participate in research studies about their experiences; however, they are often challenged in their capacity to participate as they struggle to find time for family life. In our research with parents to explore their experience of transitioning to home, we deliberately sought an approach that would reduce the imposition on parents, while gaining insightful interpretations of their experiences. This article reflects on our experience of the process of discovering, analyzing, and interpreting parents' perspectives of their journey to home, when interviewed by telephone. Applying the voice-centered relational method of qualitative analysis, accounts from parents were explored by the research team using 4 perspectives: the plot and evaluator responses to the narrative; the voice of the "I"; relationships; and placing people within cultural contexts and social structures. Parents interviewed were very receptive to being interviewed by phone. We found that this enhanced their trust in the interview process and subsequently led to our ability to gather rich data. The use of multiple lenses of analysis gave insightful interpretations of their journey to home.